Early Ovariectomy Results in Reduced Numbers of CD11c+/CD11b+ Spleen Cells and Impacts Disease Expression in Murine Lupus - Cunningham, Melissa A.; Wirth, Jena R.; Scott, Jennifer L.; Eudaly, Jackie; Collins, Erin L.; Gilkeson, Gary S. (Frontiers in Immunology, 2016)
Ninety percent of those diagnosed with systemic lupus erythematosus are female, with peak incidence between the ages of 15 and 45, when women are most hormonally active. Despite significant research effort, the mechanisms underlying this sex bias remain unclear. We previously showed that a functional knockout of estrogen receptor alpha (ERα) resulted in significantly reduced renal disease and increased survival in murine lupus. Dendritic cell (DC) development, which requires both estrogen and ERα, is impacted, as is activation status and cytokine production. Since both estrogen and testosterone levels have immunomodulating effects, we presently studied the phenotype of NZM2410 lupus-prone mice following post- and prepubertal ovariectomy (OVX) ± estradiol (E2) replacement to determine the impact of hormonal status on disease expression and DC development in these mice. We observed a trend toward survival benefit in addition to decreased proteinuria and improved renal histology in the early OVX, but not late OVX- or E2-repleted WT mice. Interestingly, there was also a significant difference in splenic DC subsets by flow cytometry. Spleens from NZM mice OVX’d early had a significant decrease in proinflammatory CD11c+CD11b+ DCs (vs. unmanipulated WTs, late OVX- and E2-repleted mice). These early OVX’d animals also had a significant increase in tolerogenic CD11c+CD8a+ DCs vs. WT. These data join a growing body of evidence that supports a role for hormone modulation of DCs that likely impacts the penetrance and severity of autoimmune diseases, such as lupus.